INTEKSUBBAND ABSORPTION OF X-POLARIZED LIGHT IN QUANTUM WELL WITH DOUBLE δ-LIKE BARRIERS - Durinyan, K. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2001)
The phenomenon of intersubband absorption of x-polarized light in quantum well with double δ-like barriers, caused by the electron effective mass coordinate dependence is considered. Analytical expressions for the oscillator strength for intersubband transitions and quantum efficiency of the optical absorption of photons under the enfluence of x-polarized light are obtained. It is shown that the absorption decreases with the increase of the opacity of surrounding δ-like barriers.